Morphologie et stabilité de la courbe du pouls d`oxygène lors d`une épreuve d`exercice cardiopulmonaire - Nickolay, T.; Ingle, L.; Hoye, A.; Garrett, A.T.; Gleadall-Siddall, D.O. (Science & Sports, 2025)
Objectives This study aimed to assess the relative and absolute reliability (agreement) of various parameters derived from the oxygen pulse (O2 pulse) curve during cardiopulmonary exercise testing (CPET), a tool critical for evaluating cardiopulmonary function and fitness.